2020
DOI: 10.1016/j.htct.2019.07.004
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective cohort study to screen linezolid-induced thrombocytopenia in adult patients hospitalized in the Midwestern Region of Brazil

Abstract: Background Thrombocytopenia (TP) is the major event associated with linezolid (LZD) therapy. We investigated the incidence and risk factors for thrombocytopenia in hospitalized adults who received LZD (1200 mg/day) between 2015 and 2017. HIV-positive, death during follow-up and those with a baseline platelet count ≤100 × 10 3 /mm 3 were excluded. Method TP was defined as a decrease in platelet count of ≥20% from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 29 publications
3
26
1
Order By: Relevance
“…In the pivotal CTs, the incidence of tedizolid-induced thrombocytopenia was 6.4% at the end of treatment visit (4), and Kim et al reported 1 patient (4%) developing thrombocytopenia out of 25 patients being treated with tedizolid during a median of 91 days (11). Here, we described thrombocytopenia in 7.4% of patients after a median of 26.5 days of tedizolid, which is in line with previous results and suggests a lower incidence than the one reported with linezolid in real-life studies (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Since anemia at baseline was common in our patients, we decided to evaluate the proportion of patients with a reduction of Ն2 g/liter of hemoglobin at any time during treatment with tedizolid.…”
Section: Discussionsupporting
confidence: 90%
“…In the pivotal CTs, the incidence of tedizolid-induced thrombocytopenia was 6.4% at the end of treatment visit (4), and Kim et al reported 1 patient (4%) developing thrombocytopenia out of 25 patients being treated with tedizolid during a median of 91 days (11). Here, we described thrombocytopenia in 7.4% of patients after a median of 26.5 days of tedizolid, which is in line with previous results and suggests a lower incidence than the one reported with linezolid in real-life studies (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Since anemia at baseline was common in our patients, we decided to evaluate the proportion of patients with a reduction of Ն2 g/liter of hemoglobin at any time during treatment with tedizolid.…”
Section: Discussionsupporting
confidence: 90%
“…According to recent studies, the incidence of thrombocytopenia ranged from 16.7-48.4% in adults treated with linezolid [4][5][6][7][8][9][10][11][12][13]. Kim et al [10] revealed a 48.3% risk of thrombocytopenia in a cohort of 60 ICU patients, and thrombocytopenia was de ned as a platelet count of < 150,000 cells/mm 3 or a decrease of at least 50% from the baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Although under longer treatment durations, linezolid-treated patients had a higher potential for lower platelet counts compared to the comparator, the difference was not statistically signi cant. However, emerging observational studies have demonstrated the thrombocytopenic effect of linezolid [4][5][6][7][8][9][10][11][12][13]. Depending on different de nitions of thrombocytopenia, the incidence of thrombocytopenia ranged from 16.7-48.4% in adults treated with intravenous or oral linezolid [4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although under longer treatment durations, linezolidtreated patients had a higher potential for lower platelet counts compared to the comparator, the difference was not statistically signi cant. However, emerging observational studies have demonstrated the thrombocytopenic effect of linezolid [4][5][6][7][8][9][10][11][12][13] . Depending on different de nitions of thrombocytopenia, the incidence of thrombocytopenia ranged from 16.7-48.4% in adults treated with intravenous or oral linezolid [4][5][6][7][8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%